Genomic prediction in hybrid breeding: II. Reciprocal recurrent genomic selection with full-sib and half-sib families - Melchinger, Albrecht E.; Frisch, Matthias; Justus Liebig University Giessen (My University, 2023)
Genomic prediction of GCA effects based on model training with full-sib rather than half-sib families yields higher short- and long-term selection gain in reciprocal recurrent genomic selection for hybrid breeding, if SCA effects are important.
Keywords: ddc:630